Kesalahan Berbahasa pada Pemberian Komentar di Media Sosial Tiktok @dedy corbuzier (Kajian Psikolingustik) - Dwi Aprilia; Fajar Setiawan; Fatmawati Fatmawati (BADAN PENERBIT STIEPARI PRESS, 2025)
This study examines language errors occurring on social media, particularly on the TikTok platform through comments on the account @Dedy Corbuzier, using a psycholinguistic approach. The background of this research focuses on the influence of language rule comprehension and social factors, such as communication trends, on language errors that reflect individuals' mental processes in communication. The research aims to identify the types of language errors that appear and to understand how psycholinguistic studies of psychological and social factors influence language use in the digital era. The method employed is a qualitative descriptive approach with literature analysis, categorizing language errors into phoneme reduction, phoneme addition, and phoneme alteration. The findings reveal that these errors frequently occur due to social environmental influences and users' tendency to disregard language rules for quick and engaging expression. The implications of this study emphasize the importance of language education that adapts to technological developments and the need for awareness regarding proper language use to enhance communication effectiveness and reduce misunderstandings in digital spaces. This study also suggests that educators and parents should be more active in teaching correct language use and encourages further research to explore the relationship between language errors and cognitive processes in social media language use.